Research on the Interaction between Eight Polyphenols and Arachin - Zuwei ZHANG; Rurui LI; Cong YANG; Yongyan MENG; Mingjuan SHEN; Jian SUN; Xuechun ZHANG (Shipin gongye ke-ji)
This study investigated the interaction between arachin and eight common polyphenols—ferulic acid, resveratrol, hesperidin, catechin, quercetin, curcumin, gallic acid, and myricetin. The interaction patterns of these polyphenols with arachin were analyzed using UV-visible and fluorescence spectroscopy, with a focus on their effects on protein structure, surface hydrophobicity and solubility. UV-visible spectroscopy revealed that the polyphenols altered the microenvironment surrounding the amino acid residues of arachin, leading to changes in its molecular conformation. Fluorescence spectroscopy identified static quenching as the quenching mechanism of polyphenols on arachin, with resveratrol and catechin demonstrating the highest binding affinity. Additionally, catechin, myricetin, and gallic acid were observed to form high-molecular-weight polymers with arachin through covalent cross-linking, verified by SDS-PAGE. Fourier infrared spectroscopy showed that polyphenols induced various conformational changes in arachin, notably increasing the proportion of α-helix, with the maximum rise reaching 36.33%. The polyphenols decreased the surface hydrophobicity and solubility of arachin, with the lowest levels dropping to 19.92 µg and 51.7%, respectively. In conclusion, the interaction between the eight polyphenols and arachin induced diverse alterations to the conformation and physicochemical properties of arachin. This study offers a scientific basis and theoretical guidance for the further processing and utilization of polyphenols and arachin.